Effects of an eight-week training program on upper-body power in women cross-country skiers - Downing, J. J.; Wilcox, A. R. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to determine if wind machine training was as effective as roller board training at increasing UBP. Forty-four women cross-country skiers, age 23-59 years, were matched on initial UBP, measured in watts (W), and placed into 1 of 2 experimental groups (roller board or wind machine). All women underwent 8 weeks of UBP training. Although both groups improved significantly pre-post (p < 0.05) in UBP, t-tests indicated that there was no significant difference (p > 0.05) between the 2 groups' improvements (roller board, pre 74.5 ± 30.9, post 95.9 ± 29.8 W; wind machine, pre 74.5 ± 33.5, post 99.3 ± 34.3 W). Thus the wind machine was as effective at enhancing UBP as the roller board.